Capecitabine-based chemotherapy in early-stage triple-negative breast cancer: a meta-analysis - Bai, Jie; Yao, Xufeng; Pu, Yinghong; Wang, Xiaoyi; Luo, Xinrong (Frontiers in Oncology, 2023)
Introduction The efficacy and safety of adjuvant capecitabine in early-stage triple-negative breast cancer remains undefined. A meta-analysis was conducted to elucidate whether capecitabine-based regimens could improve survival in early-stage triple-negative breast cancer (TNBC). Methods The current study searched Medline, Embase, Cochrane Library, Web of Science, and ClinicalTrials.gov proceedings up to 2023.9. Disease-free survival (DFS), overall survival (OS), and grade 3–4 adverse events (AEs) were assessed. Extracted or calculated hazard ratios (HRs) and odds ratios (ORs) with 95% confidence intervals (CIs) were pooled. Results The capecitabine-based regimens showed significant advantages in DFS (HR = 0.81, 95% CI: 0.73–0.90; P <.001) and OS (HR = 0.75, 95% CI: 0.65–0.87; P <.001) from 12 randomized controlled trials (RCTs) with 5,390 unselected participants. Subgroup analysis of DFS showed analogous results derived from patients with lymph node negative (HR = 0.68, 95% CI: 0.50–0.92; P = .006) and capecitabine duration no less than six cycles (HR = 0.73; 95% CI: 0.62-0.86; P <.001). Improvement of DFS in the addition group (HR = 0.77, 95% CI: 0.68–0.87; P <.001) and adjuvant setting (HR = 0.79, 95% CI: 0.70–0.89; P <.001) was observed. As to safety profile, capecitabine was associated with more frequent stomatitis (OR = 5.05, 95% CI: 1.45–17.65, P = .011), diarrhea (OR = 6.11, 95% CI: 2.12–17.56; P =.001), and hand–foot syndrome (OR = 31.82, 95% CI: 3.23–313.65, P = .003). Conclusions Adjuvant capecitabine-based chemotherapy provided superior DFS and OS to early-stage TNBC. The benefits to DFS in selected patients with lymph node negative and the addition and extended duration of capecitabine were demonstrated.